Rationale and study protocol of the Physical Activity and Dietary intervention in women with OVArian cancer (PADOVA) study: a randomised controlled trial to evaluate effectiveness of a tailored exercise and dietary intervention on body composition, physical function and fatigue in women with ovarian cancer undergoing chemotherapy - Gemma G Kenter; Ellen Kampman; Luc RCW van Lonkhuijzen; Stephanie Stelten; Meeke Hoedjes; Rosalie J Huijsmans; LM Buffart (BMJ Open)
Introduction As a consequence of ovarian cancer and its treatment, many women with ovarian cancer have to deal with reduced physical function, fatigue, and loss of weight and/or muscle mass, compromising quality of life. Exercise and dietary interventions can positively influence body composition, physical fitness and function, and fatigue in patients with cancer. However, there are no data from randomised controlled trials on the effectiveness of exercise and dietary interventions in patients with ovarian cancer. Due to a complex disease trajectory, a relatively poor survival and distinct disease-induced and treatment-induced side effects, it is unclear whether exercise and dietary interventions that were shown to be feasible and effective in other types of cancer produce comparable results in patients with ovarian cancer. The aim of this article is to present the design of the multicentre randomised controlled Physical Activity and Dietary intervention in OVArian cancer trial and to describe how the exercise and dietary intervention is tailored to specific comorbidities and disease-induced and treatment-induced adverse effects in patients with ovarian cancer.Methods and analysis Adult women with primary epithelial ovarian cancer who are scheduled to undergo first-line (neo)adjuvant chemotherapy (n=122) are randomly allocated to a combined exercise and dietary intervention or a usual care control group during chemotherapy. Primary outcomes are body composition, physical function and fatigue. Outcome measures will be assessed before the start of chemotherapy, 3 weeks after completion of chemotherapy and 12 weeks later. The exercise and dietary intervention was tailored to ovarian cancer-specific comorbidities and adverse effects of ovarian cancer and its treatment following the i3-S strategy.Ethics and dissemination This study has been approved by the medical ethical committee of the Amsterdam UMC (reference: 018). Results of the study will be published in international peer-reviewed journals.Trial registration number Netherlands Trial Registry (NTR6300).